Le portrait de presse: images et paroles d’un monde en crise - Laborde-Milaa, Isabelle (Neophilologica, 2005)
This article relies on an initial statement: during social troubled times, the news media portray series of individualized though partially anonymous actors, who are supposed to account for a collective crisis. This constitutes a kind of paradox, and brings the following question: according to which strategies, both linguistic and discursive, does a Press Portrait pretend to reflect the image(s) of this restless world? We will specifically consider different levels of tension, between the specific and generic dimensions, on the one hand, and the discourse of the newspaper and that of the social actors on the other hand. In the end, this upgrading of the individual ‘speech’ (the word is always positive) results in the setting up of archetypes; it produces a cultural reference common to all readers and, lastly, questions the relationship between portrait and the related genres in their discourse on the crisis.